The basics of the negotiating process - conceptual insights - Shaimaa Adil; Jawad kadam Alshimary (Journal of Madenat Alelem University College, 2022)
There is no doubt that the concept of negotiation is one of the old concepts in human life, although it took different names according to centuries and eras. Negotiation is a type of dialogue or exchange of proposals between two or more parties with a goal. Reaching an agreement that leads to settling an issue or disputed issues between two or several parties. Parties, and usually what takes place anywhere according to the nature of the issue and the parties calling for negotiation. Since everything is negotiable..and everyone wants to succeed, therefore success requires some effort and seriousness in work and application, a skill that enables those who master it to succeed, and accordingly the study came to clarify the nature of negotiation as an essential element, language and idiomatically, as a way to identify the most prominent characteristics of a successful negotiator and the most important Negotiating classifications to show then the most important principles that must be followed by the successful commissioner and then the necessary elements necessary for the negotiating process, ending with the most prominent successful negotiating policies and strategies, to come to the conclusion to provide us with a summary of the most important ideas with a number of conclusions reached by researchers.